ANALISIS RASIO PERBANDINGAN KINERJA KEUANGAN PT ANEKA TAMBANG TBK DAN INDUSTRINYA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2019 - Anzelina, Rahma Septi; Marsoem, Bambang Santoso (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
This study aims to determine and analyze the financial performance of PT Aneka Tambang Tbk as seen from the financial ratios. In this study, the financial performance of PT Aneka Tambang Tbk and its industry is measured using financial ratios in the form of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The research method used is descriptive quantitative. The data used are secondary data from the financial statements of PT Aneka Tambang Tbk for the period 2014 to 2019.